Novel germline JAK2R715T mutation causing PV-like erythrocytosis in 3 generations. Amelioration by Ropeg-Interferon - Song, J; Lanikova, L; Kim, SJ; Papadopoulos, N; Meznarich, J; Constantinescu, SN; Parsegov, B; Prchal, JF; Prchal, JT (Wiley, 2024)
Polycythemia vera (PV) is a clonal disorder arising from the acquired somatic mutations of the JAK2 gene, including JAK2V617F or several others in exon 12. A 38-year-old female had a stroke at age 32 and found to have elevated hemoglobin, normal leukocytes, normal platelets, and tested negative for JAK2V617F and exon 12 mutations. Next generation sequencing revealed a novel mutation: JAK2R715T in the pseudokinase domain (JH2) at 47.5%. Its presence in her nail DNA confirmed a germline origin. Her mother and her son similarly had erythrocytosis and a JAK2R715T mutation. Computer modeling indicated gain-of-function JAK2 activity. The propositus and her mother had polyclonal myelopoiesis, ruling out another somatic mutation-derived clonal hematopoiesis. Some erythroid progenitors of all three generations grew without erythropoietin, a hallmark of PV. The in vitro reporter assay confirmed increased activity of the JAK2R715T kinase. Similar to PV, the JAK2R715T native cells have increased STAT5 phosphorylation, augmented transcripts of prothrombotic and inflammatory genes, and decreased KLF2 transcripts. The propositus was not controlled by hydroxyurea, and JAK2 inhibitors were not tolerated; however, Ropeginterferon-alfa-2b (Ropeg-IFN-α) induced a remission. Ropeg-IFN-α treatment also reduced JAK2 activity in the propositus, her mother and JAK2V617F PV subjects. We report dominantly inherited erythrocytosis secondary to a novel germline JAK2R715T gain-of-function mutation with many but not all comparable molecular features to JAK2V617F PV. We also document a previously unreported inhibitory mechanism of JAK2 signaling by Ropeg-IFN-α.